Raspberries - Funt, Richard C (CABI, 2014)
Raspberries are found on every continent except Antarctica. The ﬁ rst raspberries were cultivated about 450 years ago, making raspberries a relatively new crop as compared to other fruits, such as apples or peaches. At most, two cultivars were grown in England 350 years ago. Cultivars were unnamed until after 1800. During the late 19th century and later in the 20th century, raspberry plants were taken from the ‘wild’ and from gardens and crossed to create of spring with large fruit size and disease resistance. Commercially cultivated raspberries are derived from the European red raspberry (Rubus idaeus L.) and the North American red (Rubus strigosus Michx.) and black (Rubus occidentalis L.) raspberries. While R. idaeus L. is native to Europe, it is a close relative to those in Japan and northern Asia. The American red raspberry (R. strigosus Michx.) is native to the mountain areas along the east coast (Georgia to Pennsylvania to Maine), from northern central states (the Dakotas and to the far north in Canada) and west to British Columbia, Canada. It has greater winter hardiness than the European species. Because they are so similar and hybridize easily, some taxonomists consider them to be the same species. The American black raspberry has a more southern range than the wild American red raspberry. Hybridization can occur between the black and red species, producing of spring with purple fruit. Mutations frequently occur in the red raspberry, giving rise to yellow or orange fruit. The extreme diverse nature of the genus Rubus, with hundreds of species of raspberry alone, has provided breeders the opportunity to create new kinds of cultivars by crossing among distantly related species. In US breeding programs, the ﬁ rst crosses were made at various individual state experiment stations in 1909 and at the US Department of Agriculture (USDA) at Beltsville, Maryland, Corvallis, Oregon and Cheyenne, Wyoming. Crosses were also made in Canada as early as 1893 and in England and Canada by private breeders.